2010
DOI: 10.1037/a0018274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of healthy aging and early stage dementia of the Alzheimer's type on components of response time distributions in three attention tasks.

Abstract: Objective The characteristics of response time (RT) distributions beyond measures of central tendency were explored in three attention tasks across groups of young, healthy older adults and individuals with very mild dementia of the Alzheimer’s type (DAT). Method Participants were administered computerized Stroop, Simon, and Switching tasks, along with psychometric tasks that tap various cognitive abilities, and a standard personality inventory (NEO-FFI). Ex-Gaussian (and Vincentile) analyses were used to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
194
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(228 citation statements)
references
References 109 publications
(190 reference statements)
29
194
3
2
Order By: Relevance
“…Unsworth, Redick, Lakey, and Young (2010) observed that in a sustained attention task, τ, reflecting the proportion of very slow responses, was related to measures of working memory capacity and executive control (cf. Schmiedek et al, 2007;Tse et al, 2010). The authors concluded that the slow responses reflected lapses in sustained attention (i.e., temporary loss of the task goal from working memory or brief moments of disengagement).…”
Section: Contribution Of Updating Abilitymentioning
confidence: 99%
“…Unsworth, Redick, Lakey, and Young (2010) observed that in a sustained attention task, τ, reflecting the proportion of very slow responses, was related to measures of working memory capacity and executive control (cf. Schmiedek et al, 2007;Tse et al, 2010). The authors concluded that the slow responses reflected lapses in sustained attention (i.e., temporary loss of the task goal from working memory or brief moments of disengagement).…”
Section: Contribution Of Updating Abilitymentioning
confidence: 99%
“…Del mismo modo, los resultados de variabilidad intra-individual reflejan un claro incremento de la misma en mayores y pacientes con EA, siendo superior en el caso de los pacientes. Al igual que ocurre en la tarea stroop, en un estudio posterior (Tse et al, 2010) se observa que los cambios en la variabilidad intra-individual como una función de la EA se deben únicamente a cambios en la cola lenta de la distribución de los TR, apoyando también la existencia de problemas de control ejecutivo.…”
Section: Control Inhibitoriounclassified
“…De nuevo se apunta que el incremento de la variabilidad ensayo a ensayo en las fases iniciales de la EA es consistente con las dificultades de control ejecutivo. En un estudio posterior, Tse et al (2010), utilizando esta tarea, encontraron que los cambios en la variabilidad intra-individual en función de la EA, también se debe a la presencia de valores de TR mucho más altos en la cola de la distribución correspondiente a los TR más lentos, confirmando así la existencia de problemas de control atencional.…”
Section: Cambio De Configuración Mentalunclassified
“…As some of these functions or component processes have been found to be abnormal in AD and/or MCI [94][95][96][97], generally in studies in Research Andrea Tales which participants with anxiety disorders have been excluded, the detrimental effect may be exacerbated further in individuals with various forms of anxiety. It is possible that everyday environmental interpretation and response, highly dependent upon vision and attentionrelated function, may be significant poorer in MCI and dementia compared to cognitively healthy ageing, as a result, at least in part, of concomitant anxiety in these disorders.…”
Section: Anxiety and Attention-related Processingmentioning
confidence: 99%
“…In addition to the traditional aspects of cognitive function explored in older adulthood, SCI, MCI and dementia, particularly in relation to diagnosis and progression, research has revealed that many other components and levels of information processing, particularly those related to attention [94][95][96][97], can also be abnormal in these conditions. However, the potential impact of anxiety upon such function remains a relative unknown and in the following section we highlight evidence related to the possibility that anxiety may directly or indirectly influence the results of both clinical and research tests of attention-related function.…”
Section: Anxiety and Clinical And Research Test Performancementioning
confidence: 99%